Improvement of gas barrier properties of Polyethylene Terephtalate (PET) by Graphene Nanoplatelets (GNP) - Che Mohd Noh, Mohd Ihsan; Mohamed, Mohd Ambri; Ismail, Ahmad Ghadafi; Ani, Mohd Hanafi; Majlis, Burhanuddin Yeop (Science Direct, 2019)
This research is to studies the improvement of gas barrier properties of Polyethylene Terephtalate (PET) by graphene nanoplatelets (GNP). The composite is produced by solvent casting method. The GNP content is varied from 0 wt% to 2 wt%. The optimum tensile properties of PET/GNP nanocomposite is 34.7 MPa and the reduction of gas permeation is about 99% when the PET is mixed with 2 wt% of GNP. The scanning electron microscopy (SEM) revealed that the micropores are induced in PET/GNP nanocomposite. This suggests that PET in conjunction with GNP have the potential for high gas barrier properties in food packaging.